PELATIHAN DETEKSI DINI GANGGUAN JIWA PADA KADER KESEHATAN DI DESA BUGANGAN KABUPATEN PEKALONGAN - Nafiah, Hana; Kamalah, Aisyah Dzil (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Mental disorders still become an important issue in the health sector. Problems related to mental health in the community include knowledge, stigma and mental health services. Health resources in Indonesia still has various limitation, and integrating primary services so an effort that can be solve is to integrate primary services. One of the efforts that can be made at the primary care level is the formation of mental health cadres. Health cadres need to be given training in an effort to improve cadres' abilities to manage health services, especially to providing health education directly to the surrounding community. Community service activities carried out were training on early detection of mental disorders for 25 health cadres in Bugangan Village. Cadre knowledge about mental disorders increased 28% and cadres were able to know how to do early detection of mental disorders. The output of this community service activity is the formation of mental health cadres capable of early detection of mental disorders in the community. The next community service activity is expected to be able to screening the results of early detection of the community in as a form of preventive measures for risk groups.Key words: early detection; mental health cadres; mental health problems Â